Perceived Mobile Technology Attributes, Teacher's Morale And Teaching Innovation: A Study Among Secondary School Teachers In Penang - Goon, Alex Beng Tatt (2014)
The purpose of this research is to examine the influence of perceived mobile technology attributes (learnability, simplicity, efficiency, accessibility, functionality, usability, and portability) to teaching innovation among secondary school teachers in Penang, Malaysia. Moreover, teacher’s morale has as well been used as a mediating factor in the study. The survey had been conducted among 20 national secondary schools, with 10 teachers as respondents from each school. The research had built a framework based on the Theory of Acceptance Model (TAM) and Motivational Model.